La Biblioteca de la Escuela Superior de Diplomática: la presencia de la Historia Antigua en la enseñanza española del siglo XIX a través de sus fondos - Romero Recio, Mirella (Gerión. Revista de Historia Antigua, 2005)
Even though Ancient History did not find its way into Spanish University until the 20th century, it may be traced back at the “Escuela Superior de Diplomática”, which was active from 1856 until 1900. The present study surveys the role of Ancient History within this institution, linked to the Central University (Madrid), through the analysis of the collections of its library. It must be taken into account that low budget, as well as dependency on donations, conditioned the acquisition of those books which might have been prefered by both professors and students.